Form of Abuse of The Position of Notary in Participations for Making a Sales Buying Agreement Which Causes Loss - M.Haris Aulia Riski; Hasim Purba; Suprayitno Suprayitno; T.Keizerina Devi A (Syiah Kuala Law Journal, 2021)
As a public official, a notary has to implement the provisions in article 16 paragraph (1) letter of the Notarial Act in performing his position to prepare autenthic deeds; a notary is also obliged to act honestly, be independent, be impartial and secure interest of the parties concerned in the authentic deeds prepared by the notary; which is watched and witnessed by all parties so that their aims are set forth in the deeds.